Community Adaptation to Mitigate the Impact of Flooding in Kaoliaw, Sybounhuengthong and Sysomsuen Vilages, Sykhottabong District, Vientiane Capital: https://doi.org/10.69692/SUJMRD100138 - Vanthanouvong , Phaisone; Kimmany , Bounhome; Keosouttha , Chinsamout (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Kaoliaw, Sybounhuengthong and Sysomsuen Vilages, Sykhottabong District, Vientiane Capital is one of the areas have been affected by floods every year. The main reason may be due to the geography and the location is a flat area. The construction of embankment blocked the amount of water in the area unable to be drained out, which resulted of flooding in the area. The flood problem caused people need to adapt themselves to survive. Therefore, the purpose of this research is to study the various factors that affect the occurrence of flooding and how the people adapt in the flood area. The research method analyzed the annual rainfall and the maximum of flood using Log Pearson Type III. The population sample interview was used in total of 136 families (3 villages), community's flood adaptation data is analyzed using SPSS. Research results found that the amount of annual rainfall and the number of rain days tend to decrease. SPSS illustrated that the main cause of flooding is inefficient drainage system, followed by heavy rain, which accounts for 44.5% and 20.5% of the total sample group, respectively. The maximum duration of flooding is more than 10 days, but most of them are in the range of 4 to 7 days, which accounts for almost 40% of the sample group. For the community's flood adaptation before the flood, they followed the weather news through television and social media, installed water pumping and built waterproof walls around the house; During the flood, many families had to drain the water from their houses and they have to drop their vehicles outside the flood area. After the flood, people improved their house to make it more flood resistant and plan to deal with the next flood. In addition, the study results can be an important database for relevant organizations to analyze and investigations the solution plan to deal with future floods.